International Journal Population Data Science: development and future directions - Jones, Kerina; McGrail, Kim; Schnell, Rainer; Coeli, Claudia; Lee, Stephanie (International Journal of Population Data Science, 2018)
Background and rationale The International Journal of Population Data Science (IJPDS) was launched in April 2017. It is an electronic, open-access, peer reviewed journal, publishing articles on all aspects of research, development and evaluation connected with about people and populations. It represents an internationally unique vehicle for publishing a broader range of articles than most journals in related fields by including in scope: working papers, methodological developments, informative reports, and other pieces of interest, in addition to more traditional manuscripts. As such, it provides a focal point (and a home) for all areas of Population Data Science. The creation of the IJPDS was inspired by the IPDLN, and places great importance on the viewpoints and activities of Network members to guide the development of the journal. Objective Information dissemination – stakeholder consultation – informing future directions The main objective of this collaborative session is to present the audience with an up-to-date summary of journal strategy and progress to date, and to use this forum to gain further viewpoints to better target future directions of the journal to meet the needs of those working in Population Data Science. Plan The session will comprise 5 sections: A short presentation overviewing the journal, its historical origins, its remit and relationship to the IPDLN and Network members. Primary objectives of the journal and performance metrics from the first 18 months of operation will be presented. Gauging audience opinion on: What they like/dislike about the journal What is working well/not so well Feedback and discussion on the survey results Discussions with audience in groups, each focusing on some/all of the following questions, and a question of their own choice if something arises: How can we make IJPDS articles more accessible to the general reader/non-specialist researcher? Example options: short video/audio; general reader summaries; infographics; other How can we increase the reach of, and interest in, the journal? Open answers What would you suggest as a special issue? These topics for group discussion will be posed to the session audience with the aim of using the feedback in defining our priorities for the coming year. Feedback and summing up The groups will be asked to give their feedback. Feedback from the discussions and voting will be used to inform the next steps for IJPDS. Facilitators Kerina Jones, Founding Editor-in-Chief, Swansea University, Wales Kim McGrail, Deputy Editor, University of British Columbia, Canada Claudia Medina Coeli, Editorial Board member, Rio de Janeiro Federal University, Brazil Rainer Schnell, Editorial Board member, University of Duisburg-Essen, Germany Stephanie Lee, Journal Director of Operations, Swansea University, Wales